Understanding the Influence of Personality Traits on Coping Strategies among Parents of Intellectually Disabled Children - Dondi, Amir Efrizal; Lalo, Theresia (PELNUS | Pen en Light for Natural Union of Science, 2024)
This research investigates the relationship between personality traits and coping strategies among parents of intellectually disabled children, aiming to inform the development of more effective support interventions. A sample of 200 parents participated in an online survey, providing demographic information and completing measures of personality traits and coping strategies. Results indicate significant correlations between personality traits (extraversion, conscientiousness, neuroticism, agreeableness, and openness) and coping strategies, with extraversion and conscientiousness positively associated with problem-focused coping and neuroticism positively associated with emotion-focused coping and avoidance strategies. Multiple regression analysis further highlights the predictive power of personality traits on coping strategies, controlling for demographic variables. Implications for practice include the importance of personalized support interventions, recognition of the role of social support networks, and enhancement of accessibility and integration of mental health services.